Uncertainty and exchange rate volatility: The case of Mexico - Gabriela López Noria; Georgia Bush (Banco de México, 2019)
This paper investigates the effect of uncertainty on the volatility of the Mexican peso U.S. dollar exchange rate for the period 1999 - 2018. The empirical analysis consists on estimating a model by OLS and System GMM that includes measures of economic, political, and financial uncertainty, both domestic and international, as explicative variables. The main results show that greater uncertainty leads to higher exchange rate volatility; measures of international uncertainty are found to dominate domestic uncertainty measures, although the domestic uncertainty has also an important effect on the exchange rate volatility; and there is evidence of an amplifying effect of domestic economic uncertainty on exchange rate volatility, especially during periods of recession. These results are shown to be robust to different exchange rate volatility measures, different specifications, and different economic policy uncertainty indices.
Keywords: F31; D80; D84; 330; Exchange Rate Volatility; Uncertainty; Expectations; Hyperinflation; Nachkriegszeit; Weltkrieg; Reparationen; Deutschland (bis 1945); Österreich-Ungarn; Österreich; Polen